Model Knowledge Management System Konseling Mahasiswa Berbasis Cloud Computing - H. Abdul Hamid Arribathi; Dedeh Supriyanti; Lusyani Sunarya (Universitas Raharja, 2019)
Information technology is increasingly developing and has a positive impact on the world of education. The implementation of student counseling with a Knowledge Management System is one of the contributions of information technology in the world of education. Many benefits provided by the Student Counseling Knowledge Management System, in managing the knowledge needed by the counselor section to document student consultations. The development and implementation of a KMS counseling system costs more to employ professional staff to maintain and improve; KMS student counseling application; For this reason, it is necessary to design a Cloud Computing-based Student Counseling Knowledge Management System. The research method carried out in the first stage is to collect data and information about Knowledge Management and Student Counseling, and how to use it to create a Knowledge Management System Application, Student Counseling Based on cloud computing. Furthermore, conducting a literature study and literature review, system design is in the form of data architecture compounding, process design, network design, and user interface design. The design results of this system can facilitate educational institutions in conducting online cloud computing-based student counseling